2016
DOI: 10.3390/jdb4030028
|View full text |Cite
|
Sign up to set email alerts
|

Hedgehog: A Key Signaling in the Development of the Oligodendrocyte Lineage

Abstract: The Hedgehog morphogen aroused an enormous interest since it was characterized as an essential signal for ventral patterning of the spinal cord two decades ago. The pathway is notably implicated in the initial appearance of the progenitors of oligodendrocytes (OPCs), the glial cells of the central nervous system which after maturation are responsible for axon myelination. In accordance with the requirement for Hedgehog signaling in ventral patterning, the earliest identifiable cells in the oligodendrocyte line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 94 publications
(125 reference statements)
1
38
0
Order By: Relevance
“…Noticeably, it was shown that Olig1 cre induced tdTomato fluorescence in other cell types, including motor neurons (MNs) (Figure a,b). Hh signaling has been demonstrated to play pivotal roles in the control of MN‐OPC fate switch (Traiffort et al, ), prompting us to speculate that the neonatal death of Olig1‐SmoM2 might be related to defective MN development. To evaluate the MN development in Olig1‐SmoM2 embryos, we examined the expression of MN‐specific markers, Islet1 and choline acetyltransferase (ChAT).…”
Section: Resultsmentioning
confidence: 99%
“…Noticeably, it was shown that Olig1 cre induced tdTomato fluorescence in other cell types, including motor neurons (MNs) (Figure a,b). Hh signaling has been demonstrated to play pivotal roles in the control of MN‐OPC fate switch (Traiffort et al, ), prompting us to speculate that the neonatal death of Olig1‐SmoM2 might be related to defective MN development. To evaluate the MN development in Olig1‐SmoM2 embryos, we examined the expression of MN‐specific markers, Islet1 and choline acetyltransferase (ChAT).…”
Section: Resultsmentioning
confidence: 99%
“…Biochemically, oligodendrocyte‐lineage cells express a variety of molecular markers at distinct differentiation stages. Upon lineage specification, Olig1/2, Sox10 (SRY‐Box transcription factor 10), and Nkx2.2 are substantially upregulated and persist throughout the life of oligodendrocyte‐lineage cells . Thus, these molecules are used as markers for oligodendrocyte‐lineage cells.…”
Section: Oligodendrocyte Physiologymentioning
confidence: 99%
“…Thus, these molecules are used as markers for oligodendrocyte‐lineage cells. Classical OPC markers include NG2 (neuron‐glial antigen 2), PDGFRα, and Id2/4 . It should be noted that these markers are not OPC‐specific.…”
Section: Oligodendrocyte Physiologymentioning
confidence: 99%
See 2 more Smart Citations